EFEK KONSUMSI MINUMAN BUBUK KAKAO LINDAK BEBAS LEMAK TERHADAP AKTIVITAS ANTIOKSIDAN FLAVONOID PADA PLASMA MANUSIA - Welli Yuliatmoko; Fransiska Zakaria R; Feri Kusnandar (LPPM Universitas Terbuka, 2008)
Fat free cocoa powder is a rich source of flavonoid antioxidants including epicatechin, catechin, and procyanidins, which have attracted interest regarding cardiovascular health. The aim of this research was to evaluate the effect of Indonesian fat free cocoa powder drink consumption on antioxidants activity. Healthy woman subjects were divided into cocoa group (n=9) and control group (n=9). Cocoa powder drink containing skim milk and sugar was given to the cocoa group. The control group received only water containing skim milk and sugar. The criteria of the respondents were according to health medical diagnosis and informed consent signature. Their peripheral blood was withdrawn for the analysis of antioxidants capacity. Antioxidants capacity consisted of antiradical by DPPH method, malonaldehyde (MDA) content, vitamin C, and diene conjugation. The data of cocoa group showed that there were significant increased in antiradical, vitamin C and decreased in MDA content (p<0.05). Cocoa consumption increased diene conjugation however was not significantly (p<0.05). In conclusion, the Indonesian fat free cocoa powder has increased plasma antioxidant system, which manifest good health function.